Blue LED Irradiation of Iodonium Ylides Gives Diradical Intermediates for Efficient Metal‐free Cyclopropanation with Alkenes. Issue 47 (26th September 2019) - Chidley, Tristan; Jameel, Islam; Rizwan, Shafa; Peixoto, Philippe A.; Pouységu, Laurent; Quideau, Stéphane; Hopkins, W. Scott; Murphy, Graham K.
Abstract: A facile and highly chemoselective synthesis of doubly activated cyclopropanes is reported where mixtures of alkenes and β‐dicarbonyl‐derived iodonium ylides are irradiated with light from blue LEDs. This metal‐free synthesis gives cyclopropanes in yields up to 96 %, is operative with cyclic and acyclic ylides, and proceeds with a variety of electronically‐diverse alkenes. Computational analysis explains the high selectivity observed, which derives from exclusive HOMO to LUMO excitation, instead of free carbene generation. The procedure is operationally simple, uses no photocatalyst, and provides access in one step to important building blocks for complex molecule synthesis. Abstract : Doubly activated cyclopropanes are generated upon irradiating alkenes and β‐dicarbonyl‐derived iodonium ylides with visible light from blue LEDs. This metal‐free cyclopropane synthesis works with cyclic and acyclic ylides, and with electronically‐diverse alkenes, in yields up to 96 %. Computational analysis supports a mechanism based on exclusive HOMO to LUMO excitation, instead of free carbene generation.